Text Readability and Drivers' Reading Time: Insights from the Visual Occlusion Method. (September 2013) - Ghazizadeh, Mahtab; Venkatraman, Vindhya; Torres, Miralis; Gibson, Madeleine C.; Lee, John D.; Boyle, Linda Ng
Internet access, vehicle diagnostics, and real-time communication are becoming increasingly common in all vehicles and the complexity of the information displayed is a major concern. Current guidelines focus on the number of characters in a text message, but other measures of text readability might be more sensitive. This study examined how well different metrics of text readability predict the time it takes a driver to read a message on an in-vehicle display. Participants completed reading tasks while seated in the driver's seat of a driving simulator. Occlusion goggles were used to mimic the timesharing between the driving task and the secondary reading tasks, according to the ISO 16673 (2007) guidelines. The results showed that message length (number of characters) predicts the total time spent on the task (Total Shutter Open Time [TSOT]) and that the combination of number of words in the message and Shannon entropy of the message predicts TSOT only as well as number of characters alone. Applying the model human processor calculations of reading rates (Card, Moran, & Newell, 1983) showed that participants likely read the messages word-byword in successive saccades, instead of letter-by-letter or phrase-by-phrase. Findings provide direction for more in-depth lexical analyses of text readability related to in-vehicle displays.